Wild Ecology of Spotted Deer (Axis axis) - Kushwaha, Pramod Kumar (Academic Voices: A Multidisciplinary Journal, 2018)
Chital occur in Nepal throughout the Terai lowland and adjoining Siwalik hills up to an altitude of 1200 meters. It is widely distributed and abundant in Terai protected areas of Nepal. Chital is generally found in densest and dry deciduous forest. The species display a number of preferences which influence its distribution. Four factors are limited for Chital: nee for water, need for shelter, avoidance of high rugged terrain, and the preference for grass as forage. Chital drink water at least once a day and usually twice a day during summer, which under dry conditions would tend to localize the animals around the waterhole. Academic Voices Vol.6 2016: 21-23